Management errors in adults with congenital heart disease: prevalence, sources, and consequences. (8th December 2017) - Cordina, Rachael; Nasir Ahmad, Subha; Kotchetkova, Irina; Eveborn, Gry; Pressley, Lynne; Ayer, Julian; Chard, Richard; Tanous, David; Robinson, Peter; Kilian, Jens; Deanfield, John E; Celermajer, David S
Abstract: Aims: Improved survival has resulted in increasing numbers and complexity of adults with congenital heart disease (ACHD). International guidelines recommend specialized care but many patients are still not managed at dedicated ACHD centres. This study analysed referral sources and appropriateness of management for patients referred to our tertiary ACHD Centre over the past 3 years. Methods and results: We compared differences in care between patients referred from paediatric/ACHD-trained vs. general adult cardiologists, according to Adherence (A) or Non-Adherence (NA) with published guidelines. Non-Adherent cases were graded according to the severity of adverse outcome or risk of adverse outcome. Of 309 consecutively referred patients (28 ± 14 years, 51% male), 134 (43%) were from general cardiologists (19% highly complex CHD) and 115 (37%) were from paediatric cardiology or ACHD specialists (33% highly complex CHD). Sixty referrals (20%) were from other medical teams and of those, 31 had been lost to follow-up. Guideline deviations were more common in referrals from general compared to CHD-trained cardiologists ( P  < 0.001). Of general cardiology referrals, 49 (37%) were NA; 18 had catastrophic or major complications ( n  = 2, 16 respectively). In contrast, only 12 (10%) of the paediatric/ACHD referrals were NA, but none of these were catastrophic and only 3 were major. Simple, moderate, and highly complex CHD patients were at increased risk of adverse outcome when not under specialized CHD cardiology care ( P  = 0.04, 0.009, and 0.002, respectively). Conclusion: Non-adherence with guidelines was common in the ACHD population, and this frequently resulted in important adverse clinical consequences. These problems were more likely in patients who had not been receiving specialized CHD care. Configuring healthcare systems to optimize 'whole of life' care for this growing population is essential.